Design of an infrared tomography system for detection of bubbles - Mohamad Aizat, Hashim; Yusri, Md Yunos; Ruzairi, Abdul Rahim, Prof. Dr.; Herlina, Abdul Rahim, Dr.; Muhammad Saiful Badri, Mansor; Nor Muzakkir, Nor Ayub (Penerbit UTM Press, Universiti Teknologi Malaysia., 2013)
Link to publisher's homepage at http://www.utm.my/